Occurrence and characteristics of Escherichia coli mcr‐1‐like in rabbits in Shandong, China. Issue 1 (3rd October 2020) - Wang, Xinxing; Zhai, Zhenzhen; Zhao, Xiaonan; Zhang, Hongna; Jiang, Hanming; Wang, Xuepeng; Wang, Hairong; Chang, Weishan
Abstract: Polymyxin is regarded as the last retort to fight against multidrug‐resistant (MDR) Enterobacteriaceae . The emergency and spread of polymyxin‐associated resistance gene mcr‐1 evoked great panic of no medicine to cure the bacterial infection in society. mcr‐1 is widespread in domestic and wild animals. Therefore, continuous monitoring of its prevalence and characteristics is required. In this study, we used a polymerase chain reaction (PCR)‐based method to detect the mcr‐1 of Escherichia coli isolated from rabbits of Tai'an, China, and determined the characteristics of mcr‐1‐ bearing plasmids. A total of 55 non‐duplicated E. coli was recovered from the swabs of rabbit faeces. Plasmid profiling, plasmid and chromosome PCR, complete genome sequencing, a conjugation experiment, lactose fermentation experiment, multilocus sequence typing and polymyxin resistance tests were performed to determine the characteristics of mcr‐1‐ bearing plasmids. 14.6% (8/55) of the specimens were mcr‐1 positive. The mcr‐1 ‐positive E. coli harboured more drug‐resistant genes compared with the mcr‐1 ‐negative specimens, and results showed four sequence types. Overall, these findings suggested the possible threat of the transmission of mcr‐1 from rabbits to humans, especially since the gene is located on transferable plasmids making horizontal transfer relatively easy. Since food‐producing animals are necessary for our daily diet, worldwide cooperation is needed in fighting the spread of this drug resistance gene to avoid human infections with MDR pathogenic bacteria. Abstract : The mcr‐1 ‐positive Escherichia coli were more likely to be multidrug resistance, which makes it difficult to cure. The results also suggest the possible threat of the horizontal transfer of mcr‐1 from rabbits to humans.